PHYSICAL CHARACTERISTICS OF FLY ASH NANO PARTICLES AS BACKFILL ON THE RADIOACTIVE WASTE REPOSITORY - Herry Poernomo (Universitas Gadjah Mada, 2009)
Characterization of fly ash nano particles as backfilled material candidate in the radioactive waste repository has been done. The objective of this research is to determine the permeability (K) and migration rate (Vr) of uranium in the backfilled material of fly ash, zeolite, and zeolite + fly ash mixtures. The experiment was carried out by the fixed bed method in a column contains fly ash, or zeolite, or zeolite+fly ash mixtures. It was filled with the saturated water and was flown by uranyl nitrate solution of 500 ppm as the simulated uranium. The uranium effluents was sampled in every 15 minutes and it was analyzed using spectrometer. The concentration of which represented as Ct and by using concentration profile of Co/Ct, then Vr of uranium in the backfilled material can be determined. The experiment result showed that ≤ 38 mm of fly ash particles sizes could improve the characteristic feature of 196 mm of zeolite sizes as backfilled material with the decreasing permeability values from Kzeolite = 4.06x10-3 cm/s to Kzeolite+fly ash = 5.00x10-5 cm/s and the decreasing of the migration rate from Vr zeolite = 1.65x10-4 cm/s to Vr zeolite+fly ash = 2.91x10-6 cm/second.